Invasive alien plant species of the southern part of the Nowogard Plain (NW Poland) - Konopska, Karolina (Biodiversity: Research and Conservation, 2011)
Investigations on the distribution of selected invasive plant species in southern part of the Nowogard Plain were conducted in the vegetation seasons of years 2008-2010. Field studies were based on the cartogram method. The article shows the distribution of twelve selected invasive plant species: Echinocystis lobata, Heracleum sosnowskyi, Impatiens glandulifera, Impatiens parvifora, Padus serotina, Reynoutria japonica, Robinia pseudacacia, Solidago canadensis, Solidago gigantea, Quercus rubra, Rosa rugosa and Acer negundo in the study area.